ANALISIS PENDAPATAN PETANI TUMPANGSARI DI KESATUAN PEMANGKUAN HUTAN BOJONEGORO - Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Taungya farming system has given peasants an opportunity to produce some food without getting involved in forest planting activities. It is not only cheap, but also very attractive to peoples around the forest. This report was a result of data processing of peasant's income in taungya farming system in Bojonegoro Forest District, East Java, early in 1986.The total peasant's income consists of taungya farming income, other forest activities income, and income of non forest activities. Generaly, the share of each type of income to the average total peasant's income per year is concecutively 36.8 % (Rp 57,381) of taungya farming income; 26.9 % (Rp 41,976) of other forest activities income and 36.3. % (Rp 56,473) of non forest activities income.The proportion of taungya income to total income of lnmas peasants (55.8%) is higher than Non-Inmas peasants (21.8%); whereas peasants working on a low site quality have proportion of taungya income to total income, 12.3%, which is lower than those working on a site with higher quality (50.1%).In fact, peasant's income that resultfrom forest activities, especially taungya farming still could not cope withtheir poverty. Average total income of peasants is Rp 50,814 per capita in a year or only 77 % of the minimum living standard cost only. Nevertheless, the average total income of peasants had good distribution, as far as it is concerned this would not cause an alarming trouble to the social community.